MEDIA INSTRUKSIONAL DALAM PROSES PEMBELAJARAN PENDIDIKAN ISLAM - Ermiza Ermiza; Ismail Syakban (JIP: Jurnal Ilmu Pendidikan, 2026)
Instructional media has a strategic role in increasing the effectiveness of the Islamic Education learning process. Learning that is still dominated by conventional methods tends to be less effective in accommodating the diverse needs of students, both in terms of learning styles and technological advancements. This study aims to analyze the role of instructional media in the learning process of Islamic Education and examine its contribution to increasing understanding, motivation for learning, and the internalization of Islamic values in students. The research method employed is a literature study, which involves analyzing various relevant literature sources, including books, journal articles, and previous research results. The results of the study show that the use of appropriate instructional media, including visual, audio, audio-visual, and digital media, is able to create more interactive, interesting, and meaningful learning experiences. In addition, instructional media play a supporting role in delivering teaching materials systematically and assist teachers in instilling Islamic values in a contextual manner. Thus, the optimal use of instructional media is expected to improve the quality of the learning process and outcomes of Islamic Education.